Substitution Effect on the Charge Transfer Processes in Organo-Imido Lindqvist-Polyoxomolybdate - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Gutierrez-Cutino, M; Gutierrez-Cutino, M; Canon-Mancisidor, W; Canon-Mancisidor, W; Wrighton-Araneda, K (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Two new aromatic organo-imido polyoxometalates with an electron donor triazole group ([n-Bu4N]2[Mo6O18NC6H4N3C2H2]) (1) and a highly conjugated fluorene ([n-Bu4N]2[Mo6O18NC13H9]) (2) have been obtained. The electrochemical and spectroscopic properties of several organo-imido systems were studied. These properties were analysed by the theoretical study of the redox potentials and by means of the excitation analysis, in order to understand the effect on the substitution of the organo-imido fragment and the effect of the interaction to a metal centre. Our results show a bathochromic shift related to the charge transfer processes induced by the increase of the conjugated character of the organic fragment. The cathodic shift obtained from the electrochemical studies reflects that the electronic communication and conjugation between the organic and inorganic fragments is the main reason of this phenomenon. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.